DEVELOPING METHODOLOGICAL COMPETENCE OF PRE-SERVICE EFL TEACHERS THROUGH A DIGITAL TECHNOLOGY–BASED STEP-BY-STEP TRAINING MODEL: AN INTEGRATIVE-DIDACTIC APPROACH - Erkulova Feruza Melikuziyevna (Research Focus International Scientific Journal, 2026)
This study examines the effectiveness of a digital technology–based, step-by-step training model designed to develop methodological competence among pre-service EFL teachers in a digital pedagogical environment. The model integrates diagnostic monitoring, multimodal learning resources, virtual lesson design, microteaching with video analysis, and reflective assessment through e-portfolios and learning analytics. A quasi-experimental design was employed with an experimental group receiving the intervention and a comparison group following conventional methodology instruction. Data were collected through (a) a methodological competence rubric aligned with motivational-value, cognitive-practical, reflective-analytic, and communicative-collaborative components; (b) pre/post diagnostic tests; (c) e-portfolio evidence; (d) learning analytics indicators; and (e) peer/self-assessment protocols. Results (illustrative) indicate statistically meaningful gains in the experimental group across cognitive-practical performance, reflective decision-making, and collaborative digital engagement compared with the comparison group. The findings suggest that the proposed model functions as a coherent integrative-didactic mechanism supporting iterative competence development, consistent with constructivism, reflective practice, and digital pedagogy frameworks. Implications for designing research-oriented digital methodology courses and mentoring systems are discussed.